Pedagogical knowledge: an option to investigate (Educational Perspectives Magazine (REPED), 2023)
Teachers elabórate and systematize knowledge during the mediation processes that they develop. Their mediation starts from their practice reconstructing and re-signifying it becomes a reality as a knowledge generator which has not been sufficiently studied in our educational scenarios. This leads to a theoretical vacuum that has implications in: (a) State educational policies, (b) teacher training programs in universities, and (c) educational teaching and pedagogical practice in educational institutions, to mention the most important ones. The paper is epistemologically sustained in symbolic interactionism and in complex thought and proposes an investigative process from an ethno-methodological point of view to theorize from data and in this way explain the construction of pedagogical knowledge.
Keywords: Pedagogical Knowledge, Ethno-Methodology, Symbolic Interactionism.